Long Distance Relationship: Is It Satisfactory? - Wibowo, Nur Diah Pratiwi; Harahap, Farida (Jurnal Psikologi Islam dan Budaya, 2025)
Long-distance relationships (LDRs) are often viewed as challenging in maintaining the quality of romantic relationships, especially among early adult women who are in the phase of seeking emotional stability and long-term commitment. This study aims to explore relationship satisfaction among early adult women engaged in long-distance relationships. The study employed a qualitative phenomenological approach with purposive sampling, involving four women aged 25–30 years who had been in LDRs for more than one year. Data were collected through in-depth interviews and nonverbal observations, then analyzed using data reduction and thematic coding techniques. The results show that although participants faced limited face-to-face interaction and risks of miscommunication, relationship satisfaction was maintained through effective communication, trust, and commitment. Supporting factors included problem-solving ability, partner attentiveness, and emotional understanding. Communication technology played an important role in maintaining emotional closeness. Participants viewed LDRs as a stage toward more serious, marriage-oriented relationships.